Europa vor dem Eintritt in die Wirtschafts- und Währungsunion - Bofinger, Peter; Frisch, Helmut; Issing, Otmar; Klein, Martin; Köhler, Claus; Loef, Hans-Edi; Neumann, Manfred; Vaubel, Roland (Schriften des Vereins für Socialpolitik, 1993)
Description not available